PSYCHOLOGICAL ANALYSIS OF PROTAGONIST IN ROWLING’S HARRY POTTER AND THE SORCERER STONE - Gusti Ayu Made Rai Suarniti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
The title of this paper is “Psychological Analysis of Protagonist in Rowling’s Harry Potter and The Sorcerer Stone. The aims this study were to find out the psychological problems of protagonist in it his case the problems of emotional feelings that showed in the story and also the influence of protagonist emotional feelings to his surroundings or his self. The data were collected by reading the novel thoroughly then using the note-taking technique before being identified into Psychology aspect. The collected data were descriptively analyzed by using qualitative-descriptive method to classify the types of protagonist emotional feelings and influence of protagonist emotional feelings to his surroundings or his self-found in the novel. Based on the result of the analysis, it is found there are two kinds of emotional feelings, those are: negative emotional feeling and positive emotional feeling. And the analysis he focused on the psychological analysis of protagonist in dealing with his emotion that showed in the story. According to the data, protagonist emotion can influence his surrounding and his self. It make emotional feeling become an influencer of a situation.